2007
DOI: 10.1111/j.1399-0039.2007.00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of KIR genotyping by a PCR‐SSP method that amplifies short DNA fragments

Abstract: Detection of killer-cell immunoglobulin-like receptors (KIR) genes by polymerase chain reaction with sequence-specific primers (PCR-SSP) led in 1997 to the discovery that human genomes diverge largely in the KIR they encode. While only a few KIR genes are conserved in all humans, most individuals lack several those genes, which tend to associate in diverse haplotypic combinations. The PCR-SSP technique, updated to detect the more recently identified KIR genes and alleles, is still used widely to analyze the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
149
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(152 citation statements)
references
References 50 publications
1
149
1
1
Order By: Relevance
“…Originally, our typing using primers described by Łuszczek et al 18,19 revealed relatively high representation of unusual genotype containing KIR2DL3 gene in the absence of KIR2DL1. Retyping of all KIR2DL1-negative samples with recently described primers 20 revealed the presence of KIR2DL1 gene in all KIR2DL3-positive samples, whereas KIR2DL3-negative individuals persisted negative expect for one 2DL1 þ 2DL3 À control person.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Originally, our typing using primers described by Łuszczek et al 18,19 revealed relatively high representation of unusual genotype containing KIR2DL3 gene in the absence of KIR2DL1. Retyping of all KIR2DL1-negative samples with recently described primers 20 revealed the presence of KIR2DL1 gene in all KIR2DL3-positive samples, whereas KIR2DL3-negative individuals persisted negative expect for one 2DL1 þ 2DL3 À control person.…”
Section: Resultsmentioning
confidence: 94%
“…18,19 Samples typed negative for KIR2DL1 were retyped using new primers of Vilches et al 20 Statistical analysis Differences between controls, patients and patient subgroups were estimated using the two-tailed Fisher's exact test and GraphPad InStat 3 software. The correction of P-values (if o0.05) for the number of comparisons (11 genes and 7 or 3 subgroups of patients) was calculated using the formula of Svejgaard and Ryder.…”
Section: Kir Genotypingmentioning
confidence: 99%
“…We studied by PCR 46 the presence or absence of each KIR in the genome of 224 R-MS patients and 289 healthy controls, from whom enough DNA was available. Both groups had rather similar frequencies at all KIR genes, except for KIR3DS1, under-represented among R-MS patients (OR 0.69, Po0.05, Table 4).…”
Section: Association Between Lilra3 Deletion and R-ms In Spanish Patimentioning
confidence: 99%
“…Presence or absence in the genome of each KIR gene was determined as described earlier. 46 The gene order is based on that of the KIR complex 21,53 -the genes that define the 'A' type of haplotype (KIR2DL3 through KIR2DS4) are represented in the middle, preceded and followed, respectively, by genes characteristic of the centromeric and the telomeric parts of 'B' haplotypes. Framework genes and pseudogenes found in all individuals are not shown.…”
Section: Association Between Lilra3 Deletion and R-ms In Spanish Patimentioning
confidence: 99%
“…Presence or absence of every KIR gene in the genome was assessed by PCR-SSP or PCR-SSOP. 25,26 20 were detected using the PCR primers Fa796 þ Ra925 (agcgt gaccttgtcctga and gcatctgtaggttcctcct) and Fc551 þ Rt682 (agagaggggacgtttaacc and ggtcactgggagctgaa), respectively, in the PCR conditions described elsewhere. 25 To discriminate KIR2DS3*001 from the novel allele KIR2DS3*004, we used a PCR-restriction fragment length polymorphism technique.…”
Section: Genotypingmentioning
confidence: 99%